Reclaiming Place: The Architecture of Home, Family and Migration - Horst, Heather A. (Anthropologica, 2022)
This article examines the significance of place, home and belonging among Jamaican return migrants. Drawing upon detailed case studies of return migrants who migrated to the United Kingdom in the 1950s and 1960s and moved back to Jamaica to retire over 25 years later, it explores how returnees design and use their homes to attain the dream and realities of return. Through an analysis of the structure arid design of homes that returnees spend their lives imagining and building, I reveal that, for returnees, home is not just a place, but also becomes a site for imagining several key relationships in returnees, lives that are ultimately fundamental to the act of reclaiming place.